Anti-obesity potential of selected tropical plants via pancreatic lipase inhibition - Alias, Norsyuhada; Leow, Thean Chor; Mohamad Ali, Mohd. Shukuri; Ahmad Tajudin, Asilah; Salleh, Abu Bakar; Raja Abd Rahman, Raja Noor Zaliha (MedCrave, 2017)
Natural products are a vast source of potential compounds that can be developed as anti-obesity agent. One of the mechanisms of anti-obesity agents is inhibition of pancreatic lipase. Assay of 24 crude extracts for their in vitro activity against porcine pancreatic lipase (PPL) detected four extracts demonstrating high (>70%) inhibition, seven extracts had medium (30-70%) inhibition and the remaining 13 extracts exhibited low (<30%) inhibition when incubated with PPL at a concentration of 500 μg/ml for 10 min at 37°C. Phyllanthus niruri extract displayed the most potent PPL inhibitor, followed by Orthosiphon stamineus, Murraya paniculata and Averrhoa bilimbi with the IC50 value of 27.7<34.7< 41.5<55.2 μg/ml, respectively. P. niruri & O. stamineus (the best two extracts) showed noncompetitive and uncompetitive inhibition, respectively. P. niruri & O. stamineus displayed total phenolic content of 431.0 ± 0.01 and 103.0 ± 0.01 mg GAE/g dry extract, while total flavonoid content of 14.8 ± 0.07 and 21.6 ± 0.03 mg QE/g dry extract, respectively. Both P. niruri & O. stamineus extracts showed high antioxidant activity, with EC50 values of 8.4 and 26.3 μg/ml, respectively. The results suggest that P. niruri & O. stamineus may be beneficial for obesity treatment via pancreatic lipase inhibition action.